Detection of Enterovirus D68 infection Among Malaysian population using a Preliminary luciferase-based Seroneutralization test / Nur Elena Mat Nayan - Nur Elena , Mat Nayan (2019)
Enterovirus D68 (EV-D68) is a respiratory tract pathogen which causes a range of mild to severe respiratory symptoms and in rare cases, neurological symptoms such as acute flaccid myelitis. In 2014, major outbreaks of EV-D68 occurred in several countries such as the United States and Canada, demonstrating that EV-D68 is an emerging pathogen. Therefore, studying the prevalence of EV-D68 infection in the Malaysian population is important to predict future outbreaks. In this study, a recombinant EV-D68 virus expressing a NanoLuc luciferase reporter gene (EV-D68_Nluc) was constructed using restriction enzyme-based cloning. This reporter-expressing infectious clone was used to develop a preliminary luciferase-based seroneutralization test which yields results 3 days faster than the conventional test. Subsequently, the luciferase-based test was used to assess the seroprevalence of EV-D68 neutralising antibodies (NAbs) in Malaysia using serum samples from three age groups, children (1 to 12 years old), adults (13 to 49 years old) and elderly (50 years old and above) collected in 2013, 2014 and 2015. We hypothesised that EV-D68 NAb seroprevalence would increase after 2014 in all age groups, but found a significant increase only in adults. Furthermore, we also hypothesized that EV-D68 NAb seroprevalence would increase with age. This was supported by our finding that children had significantly lower seroprevalence rates compared to adults and elderly. In addition, within the children group, seroprevalence rates increased with age: 32%, 59% and 77% in 1-3, 4-6 and 7-12 years old children, respectively. Hence, children should be prioritised in future vaccination programmes.